2007
DOI: 10.1557/proc-1019-ff04-08
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxation and Dynamic Light Scattering Study of Liposome in the Aqueous Solution

Abstract: The dynamic light scattering (DLS) has been used to investigate the diffusion behavior and the size distribution of liposome. DLS experiments show two classes of particles with their hydrodynamic radii being 4-12 nm and 66-80 nm. The numbers of particles associated with the two peaks are estimated by means of the scattering properties of the particles.Broadband dielectric spectroscopy (BDS) has been used to investigate the dynamical structure of liposome in aqueous solution of water, which makes it possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…On the other hand, the use of short and/or unsaturated acyl chains results in more fluid, liquid crystalline (L α ) bilayer structure. Experimentally, this gel-liquid crystal (LC) phase transition is well observed by changing temperature [ 26 , 27 ]. Addition of cholesterol into the lipid bilayer minimizes the effects of membrane permeability and improves the mechanical strength of the liposomes.…”
Section: Characteristics Of Liposomementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the use of short and/or unsaturated acyl chains results in more fluid, liquid crystalline (L α ) bilayer structure. Experimentally, this gel-liquid crystal (LC) phase transition is well observed by changing temperature [ 26 , 27 ]. Addition of cholesterol into the lipid bilayer minimizes the effects of membrane permeability and improves the mechanical strength of the liposomes.…”
Section: Characteristics Of Liposomementioning
confidence: 99%
“…Vesicle sizes are covered in the range of nanometer to micrometer. Spontaneously formed multilamellar vesicles (MLV) are very heterogeneous in lamellarity and size, ranging from 500 nm to 5 μ m. More sophisticated, small unilamellar vesicles (SUV, <100 nm) and large unilamellar vesicles (LUV, 100–800 nm) can be prepared by sonication or extrusion [ 27 , 33 , 35 ].…”
Section: Characteristics Of Liposomementioning
confidence: 99%
“…However, this requires more adjustable parameters. On the other hand, several authors have shown that these secondary relaxations are well described by the simpler Cole‐Cole model; this model has been successfully applied for the fitting of lateral group motions representing the β‐relaxation35, 40–42 and for describing the motion of ions ascribed to the σ‐relaxation 43…”
Section: Discussionmentioning
confidence: 99%
“…We have tried to observe a relaxation process attributed to free water with dispersing DPPC liposome in a frequency range around 20 GHz [11][12][13][14], and it was found that interactions between water and lipid bilayer bring the larger fluctuation into water molecules surrounding the lipid membrane in the liquid crystalline (LC) phase with higher mobility of lipid molecules [14]. Though the concept of lipid bilayer behaviors interacting with surrounding water has been considered, the experimental data obtained so far even in our former works were not enough to evaluate the relaxation process reflecting water dynamics at temperatures around 40 o C for the lack of higher frequency data.…”
Section: Introductionmentioning
confidence: 99%